2020
DOI: 10.1038/s41418-019-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Chchd2 regulates mitochondrial morphology by modulating the levels of Opa1

Abstract: The mitochondrion is a highly dynamic organelle that is critical for energy production and numerous metabolic processes. Drosophila Chchd2, a homolog of the human disease-related genes CHCHD2 and CHCHD10, encodes a mitochondrial protein. In this study, we found that loss of Chchd2 in flies resulted in progressive degeneration of photoreceptor cells and reduced muscle integrity. In the flight muscles of adult Chchd2 mutants, some mitochondria exhibited curling cristae and a reduced number of cristae compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…However, we cannot rule out the possibility that different complexes of these proteins are altered by CHCHD10 mutations, particularly CHCHD2, which has been reported to form a complex with CHCHD10 44,50‐52 . Interestingly, a recent study using a Drosophila model reported that the WT version of Drosophila CHCHD2 increases OPA1 levels, while CHCHD2 mutations decrease OPA1 through as yet unknown mechanism 53 …”
Section: Discussionmentioning
confidence: 89%
“…However, we cannot rule out the possibility that different complexes of these proteins are altered by CHCHD10 mutations, particularly CHCHD2, which has been reported to form a complex with CHCHD10 44,50‐52 . Interestingly, a recent study using a Drosophila model reported that the WT version of Drosophila CHCHD2 increases OPA1 levels, while CHCHD2 mutations decrease OPA1 through as yet unknown mechanism 53 …”
Section: Discussionmentioning
confidence: 89%
“…Consistent with its mitochondrial and nuclear functions, the CHCHD2 hub interactome includes the mitochondrial protein C1qBP and the oncogenic transcription factor YBX1, as identified by unbiased affinity purification mass spectrometry (Wei et al, 2015). While other studies have independently validated the functional interaction of CHCHD2 with C1qBP (Seo et al, 2010;Liu W. et al, 2020), the functional consequences of CHCHD2-YBX1 interaction are unknown.…”
Section: Regulation Of Cell Migration and Differentiationmentioning
confidence: 99%
“…Coiled-coil-helix-coiled-coil-helix domain containing 2 is thought to be involved in the maintenance of mitochondrial cristae structure via its interaction with OPA1, a protein that mediates mitochondrial inner membrane fusion in response to mitochondrial stress (Liu W. et al, 2020;Liu Y.T. et al, 2020), and its interaction with MICS1, an inner membrane protein that regulates mitochondrial morphology and cytochrome c release (Meng et al, 2017;Lee et al, 2018).…”
Section: Regulation Of Mitochondrial Structure and Apoptosismentioning
confidence: 99%
“…CHCHD2 recently gained attention as mutations in this gene have been associated with neurodegenerative diseases, including Parkinson's Diseases ( 52 ). It was proposed that CHCHD2 competes with OPA1, a dynamin-like GTPase that regulates mitochondrial fusion and cristae structure, for the binding to C1QBP/P32, a previously identified CLPX interactor ( 53 , 54 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%